A mesoporous ionic solid with 272 AuI6AgI3CuII3 complex cations in a super huge crystal lattice. Issue 33 (22nd July 2021) - Takeda, Hiroto; Kojima, Tatsuhiro; Yoshinari, Nobuto; Konno, Takumi
Abstract : A non-MOF ionic solid having two types of polyhedral mesopores in a very large crystal lattice is generated from a cationic AuI6AgI3CuII3 complex with d -penicillamine, showing specific exchanges of counter-anions retaining its single crystallinity. Abstract : Here, we report a unique mesoporous ionic solid (I ) generated from a cationic AuI6AgI3CuII3 dodecanuclear complex with d -penicillamine depending on the homochirality and crystallization conditions. I crystallizes in the cubic space group of F 41 32 with an extremely large cell volume of 2 171 340 Å 3, containing 272 AuI6AgI3CuII3 complex cations in the unit cell. In I, the complex cations are connected to each other through CH⋯π interactions in a zeotype framework, the topology of which is the same as that of the metal–organic framework in MIL-101, with similar but much larger two types of polyhedral pores with internal diameters of 38.2 Å and 49.7 Å, which are occupied by counter-anions and water molecules. Due to the cationic nature of the framework, I undergoes quick, specific exchanges of counter-anions while retaining its single crystallinity. This study realized the creation of a non-covalent mesoporous framework from a single complex salt, providing a conceptual advance in solid chemistry and material science.